Gambaran Perilaku Mahasiswa Keperawatan terhadap Isu Planetary Health on Climate Change Crisis (Overview of Nursing Students’ Behavior Toward Planetary Health on Climate Change Crisis) - Dilayatul Mukarromah (Fakultas Keperawatan, 2024)
The climate change crisis significantly impacts the decline in human health quality. Low climate-resilient behavior contributes to the worsening of this crisis. Nurses have a central role in climate change mitigation and adaptation efforts, and nursing students are expected to act as agents of change by integrating positive behaviors into clinical practice. This study aims to describe the level of nursing students' behavior regarding planetary health on climate change crisis. A descriptive quantitative study was conducted using total sampling, involving 350 undergraduate and professional nursing students from the Faculty of Nursing, University of Jember. The study utilized the Climate Health and Nursing Tool (CHANT) questionnaire, which has a Cronbach's alpha > 0.80. Data were analyzed using descriptive analysis. The results showed that the average cognitive behavior score related to climate change issues was 2.75 on a scale of 0 to 4, with the highest mean observed in the sub-indicator of concern (3.19), followed by awareness (2.80) and motivation (2.76). In contrast, the lowest mean scores were found in behavior at home (2.70) and behavior in the workplace (2.29). These findings reflect a tendency toward a moderate level of consistent behavior among nursing students, particularly in daily practical actions such as energy saving, waste reduction, and sustainable food consumption, as indicated by the mid-range position of the overall mean within the 0–4 scale. It is recommended that nursing students strengthen both internal and external factors that support consistent efforts in adapting and mitigating the impacts of the climate change crisis.
Keywords: Behavior; Climate Change; Environment; Nursing Students